2015
DOI: 10.1007/s10955-015-1436-1
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of Soft Random Geometric Graphs over Annuli

Abstract: Nodes are randomly distributed within an annulus (and then a shell) to form a point pattern of communication terminals which are linked stochastically according to the Rayleigh fading of radio-frequency data signals. We then present analytic formulas for the connection probability of these spatially embedded graphs, describing the connectivity behaviour as a dense-network limit is approached. This extends recent work modelling ad hoc networks in non-convex domains.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 26 publications
2
30
0
3
Order By: Relevance
“…Finally, a circular or spherical boundary and Gaussian connection function were considered in Ref. [42]. In all cases the results agree with the more general expressions herein.…”
Section: Comparison With Previous Results and Numericssupporting
confidence: 78%
See 1 more Smart Citation
“…Finally, a circular or spherical boundary and Gaussian connection function were considered in Ref. [42]. In all cases the results agree with the more general expressions herein.…”
Section: Comparison With Previous Results and Numericssupporting
confidence: 78%
“…Nonconvex domains with a line-of-sight condition: Examples have included keyhole geometries with [25] or without [26] reflections, circular or spherical obstacles [42], and fractal domains [43]. In the latter, remarkably, it is found that P f c decreases toward zero in the limit of high density.…”
Section: Discussionmentioning
confidence: 99%
“…This is discussed in detail on [11]. In fact, a significant amount of recent work on random geometric networks has highlighted the importance of the enclosing boundary [31,73].…”
Section: Betweenness Centralitymentioning
confidence: 99%
“…For instance, Ref. [Gil16] studied the case of circular and spherical obstacles. The effect of large obstacles is similar to that of curvature in the domain boundary; small obstacles have a differing mathematical formulation and have a small effect on connectivity unless they are very numerous.…”
Section: Obstacles and Reflectionsmentioning
confidence: 99%